A clinical study of anemia in children aged 6 months–5 years in a tertiary care center, Bengaluru, Karnataka, India - Saranappa, Siva; Wu, Jennifer (Indian Journal of Child Health, 2021)
Background: Anemia is the most commonly observed hematological diseases in children. The World Health Organization (WHO) has estimated that globally, 1.62 billion people are anemic, with the highest prevalence of anemia (47.4%) among preschool-aged children. Of these 293 million children, 89 million live in India. Aim: This study aims to evaluate the factors causing anemia in children aged between 6 months and 5 years and its prevalence within this age group. Methods: This study is a prospective observational study conducted in KIMS Hospital, Bengaluru, Karnataka. A total of 200 children in the age group of 6 months–5 years with features of anemia or having hemoglobin